2021
DOI: 10.1186/s13063-021-05295-5
|View full text |Cite
|
Sign up to set email alerts
|

Accessing routinely collected health data to improve clinical trials: recent experience of access

Abstract: Background Routinely collected electronic health records (EHRs) have the potential to enhance randomised controlled trials (RCTs) by facilitating recruitment and follow-up. Despite this, current EHR use is minimal in UK RCTs, in part due to ongoing concerns about the utility (reliability, completeness, accuracy) and accessibility of the data. The aim of this manuscript is to document the process, timelines and challenges of the application process to help improve the service both for the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Compared to traditional RCTs, those using routine data have been shown to generate additional insights [54]. However, getting access to data from administrative databases, electronic health records, and registries is often not straightforward [55]. If such data is accessible and considered in a RCT, characteristics should be reported not only for trial participants, but also for nonparticipants, as explicitly stated in CONSORT-ROUTINE item 15 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional RCTs, those using routine data have been shown to generate additional insights [54]. However, getting access to data from administrative databases, electronic health records, and registries is often not straightforward [55]. If such data is accessible and considered in a RCT, characteristics should be reported not only for trial participants, but also for nonparticipants, as explicitly stated in CONSORT-ROUTINE item 15 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving this transfer can be challenging. A recent UK study in two trials, Add-Aspirin and PATCH, found that it took 13 months for Add-Aspirin to receive data from the National Cancer Registration and Analysis Service and 15 months for PATCH to receive data from NHS Digital 20 . In another example, changing interpretation of information governance regulations by data meant that the team behind the EPOCH trial were unable to gain access to post-discharge hospital data in Wales and had to change their primary analysis because of it 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Many challenges highlighted here have been anecdotally reported in relation to specific projects or data providers [9,11,25]. Through this work, we have identified the broader current issues relating to working with administrative data, as well as developing a more detailed understanding and context around known issues by working with both researchers and data providers.…”
Section: Other Ongoing Workmentioning
confidence: 96%
“…Despite the increased availability of data and interest from funding bodies, there remain challenges for data access, storage and sharing, and difficulties in conducting crossnational research [2,[8][9][10][11]. In addition, accessing data from multiple data providers remains a challenge with different applications, requirements and governance across providers [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation